2014
DOI: 10.1017/s0268416014000150
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural specialisation and the land market: an examination of the dynamics of the relationship in the Swiss Alps, c.1860–1930

Abstract: From the latter half of the nineteenth century, mixed farming in the Alpine regions of Switzerland underwent a gradual process of specialisation. Cereal crops were phased out in favour of feed crops, livestock, viticulture and fruit farming. This article analyses the way in which the land market was affected by this increasingly specialised primary sector and asks whether this market became more efficient as a result of reduced transaction costs. Surveys have shown that the land market remained bound by the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Using Nigeria as a sample, Takeshima et al [ 3 ] found that farmers using mechanical services can release more labor force to engage in non-farming activities. Other scholars found that land was an important factor affecting grain production, such as Deininger et al [ 4 ] based on Indian and Lorenzetti [ 5 ] based on Switzerland. More research articles paid attention to soil quality and concluded that soil quality is very important to sustainable development [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using Nigeria as a sample, Takeshima et al [ 3 ] found that farmers using mechanical services can release more labor force to engage in non-farming activities. Other scholars found that land was an important factor affecting grain production, such as Deininger et al [ 4 ] based on Indian and Lorenzetti [ 5 ] based on Switzerland. More research articles paid attention to soil quality and concluded that soil quality is very important to sustainable development [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%